Cash for long‐term care: Policy debates, visions, and designs on the move. (9th May 2019) - Da Roit, Barbara; Le Bihan, Blanche
Abstract: Cash‐for‐care (CfC) schemes have introduced a key transformation in long‐term care policies across Europe since the 1990s. The article explores the extent to which CfC policies have changed over time and into which directions, the ways in which change (if any) has occurred and the forces underlying it. By combining the literature on institutional change with ideational approaches, the article focuses on policy theories and policy designs, on modes of change and factors pushing for change within the CfC policy, and in the long‐term care and neighbouring policy fields. In doing so, we aim to contribute to understanding institutional change and the transformation of an increasingly important sector of the welfare state.